Espaços arquitetônicos no processo de level design - Faggion, Lara Rubechini (My University, 2024)
The relationship between architecture and level design is undeniable and has existed since the earliest civilizations. Studies about the perception of space, carried out by architects throughout history, can be used in the creation of virtual worlds, so that the sensations and emotions experienced by players are as authentic as those experienced in the real world. Architecture can help create organized, complex, intelligible, imaginative and narrative digital environments through the spatial characteristics of the designed places. Undoubtedly, the urbanism that organizes the cities must be applied to the development of levels in games, to improve the experience of all users. [resumo fornecido pelo autor]
A relação entre a arquitetura e o level design é inegável e existe desde as primeiras civilizações. Os estudos acerca da percepção do espaço, realizados pelos arquitetos ao longo da história, podem ser utilizados na criação de mundos virtuais, para que as sensações e emoções experimentadas pelos jogadores, sejam tão autênticas quanto as vivenciadas no mundo real. A arquitetura pode auxiliar na criação de ambientes digitais organizados, complexos, inteligíveis, imaginativos e narrativos, através das características espaciais dos locais projetados. Sem dúvida, o urbanismo que ordena as cidades deve ser aplicado ao desenvolvimento de níveis nos jogos, para a melhoria da experiência de todos os usuários. [resumo fornecido pelo autor]
Keywords: Arquitetura; Espaço (Arquitetura); Level design (Ciência da computação)